Prepyloric Stricture in a 5-Year Old Infant Caused by Corrosive Injury: A Case Report - Alfi Maido Alius; Yusri Dianne Jurnalis; Jon Efendi (HM Publisher, 2022)
Background: The incidence of corrosive ingestion is high and largely unreported in developing countries due to lack of parental supervision and careless storing of these chemicals at home. Case presentation: A 5 years, 1-month-old boy came to the outpatient clinic department of pediatric Dr. M. Djamil General Hospital with a chief complaint of recurrent vomit since 6 weeks before admission. There was a history of ingested accumulator water 1,5 months before admission. The patient vomits every day, especially after eating and drinking. Conclusion: The most common symptoms are vomiting, feeding problems in oral intake, and rapid weight loss. The clinical diagnosis of prepyloric stricture is based on the history of the disease, physical examination, and supporting the investigation. Treatment of gastric outlet obstruction caused by corrosive ingestion should be treated surgically.